Enantioselective Primary Amine Catalyzed Aldol-Type Construction of Trifluoromethylated Tertiary Alcohols - Yang, Wei; Cui, Yu-Ming; Zhou, Wei; Li, Li; Yang, Ke-Fang; Zheng, Zhan-Jiang; Lu, Yixin; Xu, Li-Wen (Synlett, 2014)
It was found that the cinchona-derived primary amines and their combined catalyst systems with chiral organic acid or Lewis acid have been successfully applied in the cross-aldol reaction of trifluoromethyl ketones and aliphatic ketones. Excellent yields and good enantioselectivities (up to 89% ee) of the resulting β-trifluoromethyl-β-hydroxy ketones were obtained in the chiral primary amine catalyzed cross-aldol reaction under different conditions, which also led to both enantiomers of the desired products. This study also demonstrated the importance of synergistic effect of chiral organic acid on the primary amine catalysis.
Keywords: tertiary alcohol; primary amine; organofluorine; organocatalysis; cross-aldol reaction